The Influence of Motivation, Work Environment, and Competency on Employee Job Satisfaction at PT PLN (Persero) Bali Transmission Implementing Unit - Mantrawan, I Gusti Ngurah Puja; Rahmawati, Putu Indah; Sinarwati, Ni Kadek (Yayasan Ilomata, 2024)
Increasing employee job satisfaction has a positive impact on company productivity and performance. PT PLN (Persero) Transmission, a leading company in the energy sector, pays special attention to the factors that influence employee job satisfaction, especially motivation, work environment and competence. This research aims to analyze the influence of motivation, work environment, and competence on employee job satisfaction at PT PLN (Persero) Bali Transmission implementation unit. The population the researchers used was all permanent PT PLN (Persero) Bali Transmission Implementation Unit employees. The population in this study was 142 people who met the criteria as permanent employees of the Company, and by using the census method in selecting the sample, the research sample also numbered 142 people. Multiple linear regression analysis is applied to describe the influence of the independent variable on the dependent variable with the help of SPSS. The results of this research show that motivation, work environment, and work competence positively affect employee job satisfaction at PT PLN (Persero) Bali Transmission Implementation Unit. This means that the better the motivation, work environment and work competence simultaneously, the more job satisfaction at PT PLN Transmisi Bali will increase. This research provides implications for companies regarding employee job satisfaction and things that must be paid attention to and improved to maximize employee job satisfaction.